Gagasan dan Manifestasi Neo-Sufisme dalam Muhammadiyah: Sebuah Analisis Teoretik - Hasnan Bachtiar (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2015)
This article evaluates the concept of neo-sufism manifested in the Muhammadiyah movement. The main objective of this article is to diagnose whether Muhammadiyah intellectuals accept the concept of neo-sufism. Using philosophical study as an ap- proach, the writer argues that the religious and social concepts growing within Muhammadiyah, such as social tauhid, prophetic social sciences, and transforma- tive theology have resembled the concept of neo-sufism